Long Term Outcome After Open Abdomen Treatment: Function and Quality of Life - Theodorou, Alexis; Jedig, Agnes; Manekeller, Steffen; Willms, Arnulf; Pantelis, Dimitrios; Matthaei, Hanno; Schäfer, Nico; Kalff, Jörg C.; von Websky, Martin W. (Frontiers in Surgery, 2021)
1.1 Background Open abdomen treatment (OAT) is widely accepted to manage severe abdominal conditions such as peritonitis and ACS but can be associated with high morbidity and mortality. Main risks in OAT are 1) entero-atmospheric fistula, 2) failure of primary fascial closure, and 3) incisional hernias. In this study we assessed the long term functional outcome after OAT to understand which factors impacted most on QoL/daily living activities and the natural course after OAT. 1.2 Material and Methods After a retrospective analysis of 165 consecutive OAT patients over a period of 10 years (2002-2012) with over 65 clinical paramters had been performed at our center(1), we initiated a prospective structured follow up approach. All survivors were invited for a clinical follow up. 40 complete datasets including clinical and social follow up with SF-36 scores were available for full analysis. 2 Results Patients were dominantly male (75%) with a median age of 52 years. Primary fascial closure (PC) was achieved in 9/40 (22%) while in 88% a planned ventral hernia (PVH) approach was followed. 3/4 of the PVH patients then underwent a secondary stage abdominal wall reconstruction but 2/3 of the reconstructed patients developed recurrent hernias. 55% of the patients with PC developed an incisional hernia. 20% of all patients developed significant scarring (Vancouver Scar Score >8) and pain was reported by 15% as “moderate” (VAS 4-6) and by 10% as "severe" (VAS>7). While hernia presence, PC/PVH and scarring showed no impact on QoL, sex and especially EAF formation impacted significantly on QoL. 3 Discussion An early era approach to OAT before implementation of a structured concept (“Koblenz algorithm”) resulted in relevant mortality and morbidity. Follow up revealed that hernia incidence after OAT and secondary reconstruction is high and that 25% of patients qualifying for a secondary reconstruction did not want surgery or were unfit. Sex and EAF formation impacted significantly on QoL, which was lower than in the general population. With regard to hernia incidence, new strategies such as prophylactic mesh implantation upon fascial closure should be discussed analogous to other major abdominal procedures such as abdominal aortic repair.